NUMERICAL ANALYSIS OF DEVELOPING TURBULENT FLOW IN A CLOSED COMPOUND CHANNEL - Souza, S. I. S.; Goulart, J. N. V. (Revista de Engenharia Térmica, 2011)
The study of turbulence characteristics in compound channels is still focus of attention. A lot of experimental results have been produced. Main results have revealed a mixing layer formation between main subchannel and the gap region, implying the flow might be ruled by local scales. The outcomes have pointed to the instabilities of mixing layer are responsible for large structures formation between main channel and narrow gap. Furthermore, the periodical behavior of these structures seems to be ruled by mean mixing layer characteristics, as velocity difference, velocity of convection and mixing layer thickness. By using ANSYS-CFX-12, with unsteady Reynolds Average Navier-Stokes and as turbulence model Spalart-Allmaras (SA), a compound channel was studied. Numerical results predicted velocity profile with high vorticity peaks and flow instabilities starting at L/Dh = 15.